La forme scolaire : analyse d’un concept clé pour comprendre la difficile prise en compte de l’hétérogénéité des élèves à l’école primaire française - Sylvie Jouan (Recherches en Éducation)
The aim of this article is twofold: on the one hand, it is to review the definition of the concept of ‘school form’ and its successive clarifications in Guy Vincent's various papers. I do so by highlighting the historical, sociological and philosophical dimensions of such an approach. This enables me to stress the political and moral implications of this concept irreducible to that of structure. On the other hand, I intend to prove, by drawing on the socio-historical context in which this concept was devised, that the school form as it arose in France builds on the pedagogical model inherited from the work of Jean-Baptiste de La Salle. This model is rooted in an ideal of class homogeneity, which, from the beginnings of the republican school to the present day, has had the effect of making it very difficult to accommodate the heterogeneity of the students’ abilities. My analysis is based on the example of multi-grade classes which have long been challenged by this school form, as the latter is incompatible with the former, whose classes are inherently heterogeneous.